The old man by the waterfall: deep entanglements of culture, state-making and geopolitics in Arunachal Pradesh - Kaustubh Deka (European Bulletin of Himalayan Research)
Arunachal Pradesh, a state in Northeast India, is going through a phase of rapid infrastructural expansion, a phenomenon intensified due to the state’s geostrategic location. Despite the colonial enterprise of frontier-making and the resulting securitisation of space, the presence of the eastern Himalayan frontier has historically infused the region with elements of both steadfastness and dynamism, as its spatial fluidity persists in one form or the other. Meanwhile, despite being situated in a Himalayan corridor, the region finds itself entangled in the contentious politics in which states in South and Southeast Asia are locked. Drawing on ethnographic experiences from two geopolitically sensitive and spatially significant places, Menchukha and Namsai, situated on the eastern Himalayan slopes at Arunachal Pradesh, this article discusses the paradoxical conditions of ‘selective permeability’ (Popescu 2015: 50) that often informs contemporary border regimes, where factors favouring cross-border mobility are weighed against the demands of maintaining territorial integrity. In this context, this article looks at some prominent sites of pilgrimage and religious tourism to understand the differential attention they receive from the state, revealing a complex assemblage of spatial dynamics, cultural logics and geostrategic rationales that operate in geopolitically charged borderlands.